GraphQL in action - Buna, Samer (Manning Publications, 2021)
With thorough explorations of GraphQL concepts and numerous practical examples, this excellent book will quickly take you from novice to expert. Dary Merckens, Gunner Technology Reduce bandwidth demands on your APIs by getting only the results you need--all in a single request! The GraphQL query language simplifies interactions with web servers, enabling smarter API queries that can hugely improve the efficiency of data requests. In GraphQL in Action , you'll learn how to bring those benefits to your own APIs, giving your clients the power to ask for exactly what they need from your server, no more, no less. Practical and example-driven, this book teaches everything you need to get started with GraphQL--from design principles and syntax right through to performance optimization. about the technology GraphQL APIs are fast, efficient, and easy to maintain. They reduce app latency and server cost while boosting developer productivity. This powerful query layer offers precise control over API requests and returns, making apps faster and less prone to error. about the book GraphQL in Action gives you the tools to get comfortable with the GraphQL language, build and optimize a data API service, and use it in a front-end client application. By working through set up, security, and error handling you'll learn to create a complete GraphQL server. You'll also unlock easy ways to incorporate GraphQL into your existing codebase so you can build simple, scalable data APIs. what's inside Define a GraphQL schema for relational and document databases Implement GraphQL types using both the schema language and object constructor methods Optimize GraphQL resolvers with data caching and batching Design GraphQL fragments that match UI components' data requirements Consume GraphQL API queries, mutations, and subscriptions with and without a GraphQL client library about the audience For web developers familiar with client-server applications. about the author Samer Buna has over 20 years of experience in software development including front-ends, back-ends, API design, and scalability. A great introduction to GraphQL. This was the first book where I finally 'got it'. Jeremy Lange, G2 Learn the new API paradigm with this excellent practical guide. Isaac Wong, Privé Technologies If you want to develop an API with best practices, GraphQL is for you, and this book can help you get started quickly. Ethien Daniel Salinas Domínguez, Intelligential.tech NARRATED BY CHRISTOPHER KENDRICK.